Quantum dot 850 nm VCSELs with extreme high temperature stability operating at bit rates up to 25 Gbit/s at 150 °C. (May 2019) - Ledentsov, N.; Agustin, M.; Shchukin, V.A.; Kropp, J.-R.; Ledentsov, N.N.; Chorchos, Ł.; Turkiewicz, J.P.; Khan, Z.; Cheng, C.-L.; Shi, J.W.; Cherkashin, N.
Highlights: HPC, on-board, industrial and automotive applications require operation at high temperatures. We analyze 850 nm Quantum Dot VCSELs, capable of high-speed operation at extreme temperatures. QD VCSELs show SM polarized emission and a unique feature of increasing bandwidth with temperature. Record high speed operation is demonstrated, from 56 Gbit/s at 85 °C to 25 Gbit/s at 150 °C.